Hypoalbuminaemic hyponatraemia: a new syndrome?. Issue 6504 (2nd November 1985) - Dandona, P; Fonseca, V; Baron, D N
Abstract : Six patients with severe hyponatraemia had neurological features of hyponatraemia and pronounced hypoalbuminaemia. All had biochemical features typical of the syndrome of inappropriate secretion of antidiuretic hormone with low serum osmolality and an inappropriately high urinary osmolality. All were given infusions of whole plasma or albumin solution, or both, to restore their plasma albumin concentrations to normal, which led to a dramatic increase in plasma sodium concentrations and serum osmolality, with a concomitant fall in urinary osmolality in all patients. Neurological features were reversed in four patients. It is suggested that severe hypoalbuminaemia is an important cause of appreciable hyponatraemia; infusions of plasma and albumin in such patients may reverse the biochemical and clinical features and should form the basis of management.